Analysis of Present and Future Financial Viability of High-Concentrating Photovoltaic Projects - Tomosk, Steve; Wright, David; Hinzer, Karin; Haysom, Joan E. (Université d'Ottawa | University of Ottawa, 2015)
Three metrics for the financial analysis of high-concentrating photovoltaic (HCPV) systems are assessed: capital costs for fully installed systems (in $/W), the levelized cost of electricity [in $/kilowatt-hours (kWh)], and the net present value [NPV (in $)]. First, capital costs for HCPV systems are shown to have fallen at a steady rate and are characterised by a learning rate of 18 % with a 90 % confidence interval of 14–22 %. The analysis further combines this learning rate with future scenarios for volume growth rates to provide “lower,” “middle,” and “upper” projections for future capital costs of HCPV systems. These capital cost projections are used as inputs to the LCOE and NPV calculations, from which present and future project viability is assessed for a number of different project conditions. A case study for an HCPV deployment in Las Vegas exhibited an LCOE of $0.125/kWh in 2014 under the “middle” capital cost scenario, which decreases to $0.072/kWh by 2020. For project locations and situations where electricity rates vary according to different hours of the day, the NPV calculation provides a better assessment of financial viability. A detailed methodology with month-hour computation of revenues was developed and applied to two offsetting case studies: Las Vegas, Nevada (with time-of-use electricity prices for small businesses) and Ottawa, Ontario (with a large business rate structure that depends on peak demand). HCPV provides a good match for peak demand times, and the correspondingly high tariffs improve profitability compared with flat electricity rates. Both case studies exhibited profitability by 2015 (2018) under the “low” (“middle”) capital cost scenarios. The research as a whole indicates that HCPV systems are already competitive with other solar energy technologies and in certain locations may already be able to deliver market-competitive electricity costs. As prices continue to fall between now and 2020, many more projects will be profitable in both high- and low-DNI locations depending on the electricity rates and their structure.